2023
DOI: 10.1021/acs.energyfuels.3c00717
|View full text |Cite
|
Sign up to set email alerts
|

Minireview Elaborating S-Scheme Charge Dynamic Photocatalysts: Journey from Z to S, Mechanism of Charge Flow, Characterization Proof, and H2O2 Evolution

Abstract: In recent years, S-scheme oriented photocatalytic systems have shown tremendous potential and possibilities toward efficient conversion of solar energy to clear and sustainable chemical fuel owing to superior exciton separation and strong redox ability. This minireview summarizes the background history of the S-scheme mechanism along with a brief discussion of the type of band alignment and the journey from Z-scheme type to Sscheme systems. The review also elaborates the detailed operational mechanism and bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The benefits of this technique are (i) a facile reaction setup and (ii) a cost-effective nature, as well as the involvement of renewable feedstocks as per technological and economical aspects. , The immense increment in the study of this process is reflected by the large number of related kinds of literature. The O 2 photoreduction over the catalyst surface goes via two pathways: (i) a single-electron two-step route characterized by the superoxide radical intermediate (O 2 + e – → • O 2 – , • O 2 – + e – + 2H + → H 2 O 2 ) and (ii) a single-step two-electron direct route (O 2 + 2e – + 2H + → H 2 O 2 ). The dominance of either pathway can be confirmed by the intermediate scavenging test and conduction band potential of the material. Above all, the photocatalytic tactic is still associated with certain drawbacks (i.e., faster carrier recombination, low light absorption, selectivity, etc.)…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The benefits of this technique are (i) a facile reaction setup and (ii) a cost-effective nature, as well as the involvement of renewable feedstocks as per technological and economical aspects. , The immense increment in the study of this process is reflected by the large number of related kinds of literature. The O 2 photoreduction over the catalyst surface goes via two pathways: (i) a single-electron two-step route characterized by the superoxide radical intermediate (O 2 + e – → • O 2 – , • O 2 – + e – + 2H + → H 2 O 2 ) and (ii) a single-step two-electron direct route (O 2 + 2e – + 2H + → H 2 O 2 ). The dominance of either pathway can be confirmed by the intermediate scavenging test and conduction band potential of the material. Above all, the photocatalytic tactic is still associated with certain drawbacks (i.e., faster carrier recombination, low light absorption, selectivity, etc.)…”
Section: Introductionmentioning
confidence: 94%
“…24,46 As we know, the faster charge carrier recombination in a photocatalytic system is the major issue that substantially reduces the overall efficiency of the material in different photocatalytic applications. 15,53,54 To address this problem, various strategies were developed and implemented from time to time, but still the benchmark efficiency was not achieved. However, via piezopolarization, this carrier recombination rate in piezophotocatalytic systems has been subsided to a significant extent, resulting in noticeable improvement in overall activity.…”
Section: Fundamentals Insights Into Piezocatalysis and Piezo-photocat...mentioning
confidence: 99%
“…UV-light irradiation of TiO 2 promotes the electrons in the valence band (VB) to the conduction band (CB). The VB holes with very strong oxidation ability (E VB = +2.89 V at pH 3) 13 oxidize H 2 O 2 to O 2 and H + (E = +0.518 V at pH 3, eqn (7)). 14 Rothschild, Warren, and co-workers reported that the hole transfer from the VB of α-Fe 2 O 3 to H 2 O 2 can occur with ∼100% efficiency.…”
Section: Basic Working Principle Of H 2 O 2 -Pfcsmentioning
confidence: 99%
“…1 Among them, photocatalytic synthesis of H 2 O 2 via molecular oxygen reduction and/or water oxidation can be a highly promising one-step process at ambient temperature and pressure. [2][3][4][5][6][7] On the other hand, H 2 O 2 has attracted much interest as an energy carrier because of the large 23.6 kg m −3 volumetric hydrogen density (35.5% aq. ), which is ∼300 times the value of hydrogen (0.0818 kg m −3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various heterojunction types have been pursued as compelling strategies for broadening the light absorption range and attaining efficient electron–hole separation. Among these, the Z-scheme heterojunction is reported to be beneficial in attaining both charge separation efficiency and strong redox ability. When proper semiconductors are chosen for the Z-scheme, the charge transfer direction is adjusted to lower the conduction band (CB) and raise the valence band (VB) in the spatially separated positions, promoting redox reactivity. To fully leverage the Z-scheme, the efficient charge transfer between heterophotocatalysts is important. For this, the Z-scheme constructed with p-type and n-type semiconductor junctions can facilitate the charge transfer by the enhanced electric field. However, there exist evident constraints in the complete adoption of this strategy to MOF-based photocatalysts, owing to the rather insulating property of MOFs, which restricts the efficacy of the electric field generated at the heterojunction interface. , …”
Section: Introductionmentioning
confidence: 99%